Laboratory Tools to Quantify Biogenic Dissolution of Rocks and Minerals: A Model Rock Biofilm Growing in Percolation Columns - Seiffert, Franz; Bandow, Nicole; Kalbe, Ute; Milke, Ralf; Gorbushina, Anna A. (Frontiers in Earth Science, 2016)
Sub-aerial biofilms (SAB) are ubiquitous, self-sufficient microbial ecosystems found on mineral surfaces at all altitudes and latitudes. SABs, which are the principal causes of weathering on exposed terrestrial surfaces, are characterised by patchy growth dominated by associations of algae, cyanobacteria, fungi and heterotrophic bacteria. A recently developed in vitro system to study colonisation of rocks exposed to air included two key SAB participants - the rock-inhabiting ascomycete Knufia petricola (CBS 123872) and the phototrophic cyanobacterium Nostoc punctiforme ATCC29133. Both partners are genetically tractable and we used them here to study weathering of granite, K-feldspar and plagioclase. Small fragments of the various rocks or minerals (1 to 6 mm) were packed into flow-through columns and incubated with 0.1% glucose and 10 µM thiamine-hydrochloride (90 µL.min-1) to compare weathering with and without biofilms. Dissolution of the minerals was followed by: analysing (i) the degradation products in the effluent from the columns via Inductively Coupled Plasma Spectroscopy and (ii) by studying polished sections of the incubated mineral fragment/grains using scanning electron microscopy, transmission electron microscopy and energy dispersive X-ray analyses. K. petricola/N. punctiforme stimulated release of Ca, Na, Mg and Mn. Analyses of the polished sections confirmed depletion of Ca, Na and K near the surface of the fragments. The abrupt decrease in Ca concentration observed in peripheral areas of plagioclase fragments favoured a dissolution-reprecipitation mechanism. Percolation columns in combination with a model biofilm can thus be used to study weathering in closed systems. Columns can easily be filled with different minerals and biofilms, the effluent as well as grains can be collected after long-term exposure under axenic conditions and easily analysed.